In the Beginning Was the Deed : Realism and Moralism in Political Argument - Williams, Bernard, 1929-2003 (Book collections on Project MUSE., 2008)
Bernard Williams is remembered as one of the most brilliant and original philosophers of the past fifty years. Widely respected as a moral philosopher, Williams began to write about politics in a sustained way in the early 1980s. There followed a stream of articles, lectures, and other major contributions to issues of public concern--all complemented by his many works on ethics, which have important implications for political theory.